Chronic oil pollution harms Magellanic penguins in the Southwest Atlantic - Garcia Borboroglu, Jorge Pablo (2006)
Petroleum pollution is a problem for seabirds along the Southwest Atlantic coast. Twenty-five groups from Salvador, Brazil (12º58´S) to San Antonio Oeste, Argentina (40º43´S) survey or rehabilitate sick or oiled seabirds. Four groups, one each in Brazil and Uruguay, and two in Argentina, kept counts of birds found alive and in need of rehabilitation. An average of 63.7% of the seabirds found were Magellanic penguins (Spheniscus magellanicus), with 3869 reported since 1987. Mainly adult penguins were found in Argentina (1605 of 2102 penguins of known age class) and Uruguay (158 of 197). Juveniles were most common in Brazil (234 of 325). Oil fouling was the most frequent cause of injury or sickness. The number of oiled penguins reported in their wintering range has greatly increased since the early 1990s and is strongly correlated with petroleum exports from Argentina. Our results show that chronic petroleum pollution is a problem for wildlife from Southern Brazil through Northern Argentina, and regulations and enforcement are failing to protect living resources.